Evaluation of drought response of two poplar clones (Populusxcanadensis Monch 'I-214' and P. deltoides Marsh. 'Dvina') through high resolution analysis of stem growth - Giovannelli, Alessio; Deslauriers, Annie; Fragnelli, Giuseppe; Scaletti, Luciano; Castro, Gaetano; Rossi, Sergio; Crivellaro, Alan (Journal of Experimental Botany, 2007)
Different irrigation effects on stem radius variation (Δ R ) and maximum daily shrinkage (MDS) in Populus deltoides ‘Dvina’ and Populus×canadensis ‘I-214’ were studied to assess differences in drought tolerance between clones. One-year-old trees growing in concrete tanks were submitted to two irrigation regimes (natural rainfall and irrigation) from 24 June to 10 August, and Δ R was monitored by automatic point dendrometers. Independently of the irrigation regime, ‘Dvina’ showed a higher stem radial increment than ‘I-214’. In both clones, the first response to changed soil water content was a significant increase in MDS, whilst Δ R decreased about 20 d later when pre-dawn leaf water potential (Ψpd) dropped below –0.4 MPa. However, they displayed different strategies to overcome drought. ‘Dvina’ maintained a positive Δ R for longer than ‘I-214’, which had lower leaf Ψpd and greater leaf abscission at the end of the drought period. After irrigation resumed, ‘Dvina’ showed a higher capacity to restore stem growth. ‘I-214’ was probably unable to recover secondary growth because of higher leaf abscission during drought stress and the production of newly expanded leaves during recovery. It is concluded that the larger radial growth of ‘Dvina’ derived from a better water use (carbon uptake versus water loss) than ‘I-214’ under limited water availability.